1998
DOI: 10.1016/s0741-5214(98)70133-8
|View full text |Cite
|
Sign up to set email alerts
|

Can intrarenal duplex waveform analysis predict successful renal artery revascularizaion?

Abstract: Although we do not believe that duplex sonographic measurement of intrarenal flow patterns alone is an accurate means of assessing main renal artery occlusive disease, the resistive indices seem to reflect the magnitude of intraparenchymal disease, and thus may provide important prognostic information for patients undergoing surgical revascularization. Our data suggest that a preoperative d/s ratio below 0.3 correlates with clinical failure relative to BP and renal function responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 36 publications
0
13
0
3
Order By: Relevance
“…Moreover, resistive index appears to correlate, at least in part, with transplant renal allograft function and may serve as a marker of rejection 20. Others have examined the ability of resistive index to predict outcomes after renal artery revascularization for patients with renovascular disease 21-23. These studies identified resistive index >0.8 or 0.7 (diastolic-systolic ratio <0.3) to be associated with worsened clinical responses to renal artery revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resistive index appears to correlate, at least in part, with transplant renal allograft function and may serve as a marker of rejection 20. Others have examined the ability of resistive index to predict outcomes after renal artery revascularization for patients with renovascular disease 21-23. These studies identified resistive index >0.8 or 0.7 (diastolic-systolic ratio <0.3) to be associated with worsened clinical responses to renal artery revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recent studies from select patient populations have demonstrated strong associations between Doppler-derived measures from the renal parenchyma and the severity of hypertension, the risk of progressive renal failure, and the risk of death. [8][9][10]12,20,21 Moreover, we have demonstrated strong associations between Doppler-derived measures from the renal parenchyma and the severity of elevated blood pres- sure and decreased serum creatinine in a population-based cohort of elderly Americans. 15 This retrospective review of patients with severe hypertension, with or without renal insufficiency, who underwent open operative repair or percutaneous intervention demonstrated no apparent association between the RI and hypertension response.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, studies have described significant correlation between Doppler-derived parameters from renal duplex sonography (RDS) of segmental renal vessels and the renal parenchyma, and response to intervention for AS-RVD. [7][8][9][10][11][12] Although we have found RDS to be both accurate and reliable for the determination of hemodynamically significant main renal artery stenosis or occlusion, we have not used features of the Doppler spectrum to select patients for intervention. [13][14][15] Given the overall accuracy of RDS as a screening study for anatomic disease, if the Doppler spectral analysis could provide indication of both the hemodynamic and the functional significance of AS-RVD, the utility of RDS would be further enhanced.…”
mentioning
confidence: 99%
“…Renal function response was evaluated with the use of the decrease in serum creatinine level as a criterion. 14,15 As Zeller et al 14 reported in their study, the results with this strict criterion provide a conservative estimate of the true benefit of renal revascularization. Improvement in renal function was defined as a reduction in creatinine levels of at least 15%, and worsening was defined as creatinine levels of greater than 15% higher than pretreatment values.…”
Section: Follow-upmentioning
confidence: 95%